Wireless Incubators and Photodynamic Therapy Enhance Premature Infant Care: Inkubator Nirkabel dan Terapi Fotodinamik Meningkatkan Perawatan Bayi Prematur - Yusur Jawad Kadhim (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the critical health challenges faced by premature infants by developing an innovative, wirelessly controlled incubator using Arduino technology. By maintaining optimal environmental conditions (37°C and 50% humidity), similar to a mother's womb, and utilizing photodynamic therapy with a 400nm wavelength light to treat jaundice, our system reduces the risks associated with traditional wired setups and operational costs. The results demonstrate effective regulation of temperature and humidity, as well as a reduction in bilirubin levels, suggesting that this technology has significant potential to enhance neonatal care for premature infants. Highlights: Wireless control systems in incubators improve safety and reduce the complexity and cost associated with traditional wired setups. Photodynamic therapy effectively reduces bilirubin levels, addressing jaundice in premature babies. Maintaining optimal incubator conditions of 37°C temperature and 50% humidity mirrors the environment of a mother’s womb, enhancing survival rates. Keywords: Premature Infants, Wireless Technology, Incubator, Photodynamic Therapy, Neonatal Care